Benzylic C(sp3)–H fluorination - Atkins, Alexander P.; Dean, Alice C.; Lennox, Alastair J. J. (Beilstein Journal of Organic Chemistry, 2024)
The selective fluorination of C(sp3)–H bonds is an attractive target, particularly for pharmaceutical and agrochemical applications. Consequently, over recent years much attention has been focused on C(sp3)–H fluorination, and several methods that are selective for benzylic C–H bonds have been reported. These protocols operate via several distinct mechanistic pathways and involve a variety of fluorine sources with distinct reactivity profiles. This review aims to give context to these transformations and strategies, highlighting the different tactics to achieve fluorination of benzylic C–H bonds.
Keywords: benzylic; C–H functionalization; fluorination; photoredox catalysis